Development of Fotar (Photosynthesis Augmented Reality) Learning Media to Improve Science Literacy Skills in Elementary School Students - Ahda Alifia Rahmah Jamhari; Samsul Maarif (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2025)
Science literacy is crucial in 21st-century education but remains low among Indonesian elementary students due to ineffective teaching methods and unengaging media. This study developed and evaluated FotAR (Photosynthesis Augmented Reality), an AR-based learning media designed to enhance science literacy in elementary students. Conducted at SDN Baru 06 Pagi, East Jakarta, the research used the Borg and Gall R&D model. Data collection methods included expert assessments, the use of questionnaires, and administration of pre- and post-tests. Results showed high feasibility with scores of 97.5% from media experts and 89.5% from content experts. Student and teacher responses were also very positive, with practicality ratings of 98% and 80%, respectively. A gain score of 0.72 indicated significant improvement in learning outcomes. The findings suggest that FotAR effectively supports students' understanding of photosynthesis and improves their engagement and scientific thinking. This study concludes that AR-based learning media can be a powerful tool to enhance science literacy in elementary education.